Analisis Return, Risk dan VaR Portofolio Saham JII dengan Metode SIM, MAD dan DD - Rohiman Atja; Indupurnahayu; Renea Shinta Aminda (Department of Islamic Economics, IPB University, 2022)
Before pandemic, Islamic stocks performance (ISSI, JII70, JII) contracted. During pandemic, outperformed JCI and LQ45. JII prospect is good this year, increase 5.81% early 2021, exceeded JCI (4.66%) and LQ45 (4.75%) ytd. This study uses 4 investment scenarios aimed at analyzing and exploring the Return and Risk of the selected JII Portfolio using SIM, MAD, and DD Methods; perform calculations and analyze VaR of the selected JII Portfolio; calculate and analyze the relationship between Return and Risk of the selected JII Portfolio using SIM, MAD, and DD Methods; calculate and analyze the differences in Return and Risk of the selected JII Portfolio using the SIM, MAD, and DD Methods. The research methods are SIM, MAD, DD, VaR, Correlation-Test and Difference-Test. The results of the study of the highest return of each method resulted in scenario 2, the highest risk of each method resulted in a scenario of 33.3% investment proportion, the highest VaR resulted in scenario 2. Test-correlation method in calculating returns: there is no significant relationship between the SIM-MAD and DD-MAD methods, there is a significant positive relationship between the SIM-DD method.